Obtenção de produto farináceo a partir de beterrabas submetidas à secagem estacionária - Araujo Filho, Djalma Gomes de (2008)
The production of dried vegetables has increasingly due to longer service compared to conservation in natura, the practicality of use and the possibility of use of surplus production, reducing effects of seasonality. The search is proposed to develop a beet flour using simple technology and procedures available for the majority of small producers. It was compared different types of longitudinal and transverse cuts of beet (long 2mm; long 4.5mm; long 9mm, and, trans 2mm; trans 4.5mm; trans 9mm) as the time for air-drying, drying rate, time in the grounding process, income in flour product and its size. The conditions for the material drying, the cooked slices (2 mm) of beet, were similar, so it was recommended among the treatments the use of 100° C for 2 hours and 70° C to the end, for this condition finishes the process of air-drying in temperature more lenient. The treatments showed no significant difference in income for the full production of flours and brans, but the flours were significantly different as to size. Minors were drying times of the treatment of cuts 2 mm (7.3 h = longitudinal, 7.3 h = transverse) and sticks 4.5 mm (7.3 h = longitudinal, 7.7 h = transverse). The treatments in sticks 9mm remained, longitudinal = 9.7 h and transverse = 9.3 h, in the air-dryer. The beet flour showed percentage posted for nutrients, carbohydrate (50.32 to 5.39%), dietary fiber (23.30 to 26.90%), protein (11.32 to 13.40%) and total of minerals (4.70 to 6.82%). Already, the level of lipids, as expected, was less than 0.75%. Considering the ease of slices preparation, the dry time, the production of low size flour, and the flour income, the treatment that produced cooked slices of beet in sticks of 4.5 mm in thickness was recommended to the flour processing.